Pendidikan Karakter di Lingkungan Pondok Pesantren Al-Imaroh Berpedoman pada Uswatun Hasanah - Izzah, Azmi Nur; Sodiq, Ahmad; Khalimi, Khalimi (Arfannur: Journal of Islamic Education, 2025)
This research reveals that attention to aspects of religious behavior in Islamic Religious Education (PAI) is still lacking, with more focus on cognitive aspects. This research aims to determine: 1) The muhasabah-based religious habituation method program at SMAN 2 Cikarang Utara, 2) The condition of students' spiritual intelligence, and 3) Supporting and inhibiting factors for its implementation. The research uses a qualitative approach with case study and analytical descriptive methods. Data was collected through observation, interviews, questionnaires and documentation. The results show that the muhasabah method involves group prayer, Duha prayer, recitation of the Koran, lectures, and social activities to shape character. Students' spiritual intelligence is generally good, influenced by family support and personal motivation, but hampered by lack of family communication, negative environmental influences, and minimal understanding of religion. Supporting factors include school leadership, quality of teaching, positive environment, and family support. Inhibiting factors include lack of motivation, family support, and negative environmental influences. Collaboration between schools, families and communities is needed to overcome obstacles and increase students' spiritual intelligence.